WOMAN'S FIGHT FOR EMANCIPATION AS REFLECTED IN CHARLOTTE BRONTE'S JANE EYRE - Alfianti Charmenita Lahinda; Paula L. Hampp; Imelda S. Lolowang (SoCul: International Journal of Research in Social Cultural Issues, 2021)
This study aims to analyze woman's fight for emancipation in Jane Eyre novel by Charlotte Bronte, a novel written in the Victorian era and first published in 1847. Woman emancipation refers to woman's struggle to obtain rights that should be given in order for her potential to develop and function fully in certain aspects of life. In this study, the writers use qualitative research because the data are gathered in the form of words rather than numbers. The mimetic approach also employs in order to seek woman’s fight for a better life. There are two kinds of sources namely primary and secondary sources. The primary source is the novel itself whereas the secondary sources are from books and internet references. The result of the analysis shows Jane Eyre’s fight for woman emancipation, she has authority and freedom as a human being who is fully entitled to herself, and is able to decide the best path for herself. By using the feminism theory of Betty Friedan in The Feminine Mystique, it can be concluded that Jane Eyre is able to show her ability and become a female character who can be an excellent role model in the fight for emancipation.